2019
DOI: 10.5713/ajas.18.0408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary humic acid and enzymes on meat quality and fatty acid profiles of broiler chickens fed canola-based diets

Abstract: It can, therefore, be concluded that CM can be included in broiler diets in the presence of enzymes and humic acid with positive effects on meat quality and important fatty acids that are beneficial to the health of consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
3
16
1
Order By: Relevance
“…Our findings about the effect of HS on decreasing pH trend are also confirmed by the results of Aksu et al. (2005) and partially by Disetlhe et al. (2019) , which also indicate a decrease in pH after feeding with HS.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings about the effect of HS on decreasing pH trend are also confirmed by the results of Aksu et al. (2005) and partially by Disetlhe et al. (2019) , which also indicate a decrease in pH after feeding with HS.…”
Section: Resultssupporting
confidence: 87%
“…The optimal sensory quality for broiler meat is usually reflected in meat color, tenderness, and water-holding capacity ( Yang et al., 2011 ). The visual appearance of meat is one of the most vital meat quality attributes that influence visual acceptance of meat and meat products and subsequently, purchasing decisions by consumers ( Disetlhe et al., 2019 ). Although the precise underlying mechanism of the effect of HS is unknown, it appears that HS contain minute quantities of several minerals, including Fe, Mn, and Cu, which may influence meat color ( Ji et al., 2006 ) and subsequently the consumers choice through the visual acceptance of the product.…”
Section: Resultsmentioning
confidence: 99%
“…Disetlhe et al 2019, who fed chickens with humic acid, found similarly as in our experiment, found increased levels for most PUFAs, and a similar tendency was also found in groups with supplement of garlic and oregano powder. We no found higher differences (P≥0.05) in the PUFA content of the breast muscle after the addition of humic acid and garlic or oregano powder, but in the thigh muscle were higher value (P≤0.05) in experimental group with supplementation of the humic acid and garlic powder than in the control as reported by Disetlhe et al (2019). In the study Choi et al (2010) results show that 3 and 5% garlic powder or 3% garlic powder plus αtocopherol supplementation to diets can effectively change the fatty acid composition by increasing or protecting the oxidation of unsaturated fatty acid and total unsaturated fatty acid because palmitic and oleic acids are the main fatty acids of the thigh muscle, what is comparable to our results.…”
Section: Resultssupporting
confidence: 56%
“…The use of antibiotics in animal production has led to a dramatic decline in the prevalence of diseases; however, issues with medication residues have hindered the implementation of antibiotic treatment regimens. Currently, health management and biosecurity represent important practices in animal production [ 1 , 2 ]. Humic acid (HA) is a natural organic product derived by chemical and biological processes from dead plants and animal tissues.…”
Section: Introductionmentioning
confidence: 99%